Consumer motives influencing the competitiveness of pharmacies in municipal dimensions - Hortolányi, Árpád László (Studia Mundi – Economica, 2023)
Pharmacies compete in a specialized market where, in addition to fulfilling important public duties, ensuring profitability is also a top strategic priority. To achieve long-term profitability, market players can relocate their operations to a central region, subject to certain constraints, but this step leaves significant areas without access to medication. The dual expectation requires pharmacies to develop a specific strategy that simultaneously ensures profitable operations while maintaining the safety of access to medication. In my research, I sought to determine whether there are characteristics that can be isolated, based on population differences in different types of settlements, which can help pharmacies develop a successful competitive strategy. In the primary research, I used standard questionnaire-based inquiries to identify the most important consumer preferences related to pharmacy choice, which I then examined in relation to the territorial dimensions. The analysis shows that consumers in areas with different characteristics have unique expectations of a pharmacy, therefore, developing a successful competitive strategy requires integrating the needs and preferences of the population in the region.
Keywords: pharmaceutical market; competitiveness; consumer preferences